Condition of Coral Reefs and Reef Fishes in Dofa Village, Sula Islands Regency - Alimuddin Alimuddin; Nurul Chayati; Tedy Murtejo; La Ode M. Gunawan Giu; Ria Fitri (Politeknik Negeri Batam, 2021)
Coral reefs are unique among ocean associations or communities that are entirely formed by biological activity. This study aims to determine the condition of coral reefs and reef fishes in Dofa Village, West Mangoli District, Sula Islands, 2018. Collecting coral data used the Line Intercept Transect (LIT) method, while coral fish data collection used the visual census method. Water parameters measured are temperature, salinity, degree of acidity (pH), brightness and current velocity. Based on observations, the water temperature ranges from 29.33° C - 29.9° C. The salinity of the waters ranges from 29.67 ‰ - 34 ‰. The degree of acidity is 7.5 which supports the life of coral reef. The water brightness level is 65% - 100%. The current velocity ranges from 0.02 m / s to 0.05 m / s. The condition of the coral reef ecosystem based on the percentage of hard coral cover ranged from 21.02% - 33.7% with low to medium category. The coral mortality index at the study location was small where at station 1 it was 0.487, station 2 was 0.335 and station 3 was 0.205, meaning that there was no significant change for live coral reefs. The abundance of reef fishes ranged from 0.52 ind/m2 - 1.22 ind/m2 which was dominated by the Pomacentridae and Labridae families where the two families were groups of fish that used coral reefs as habitat for feeding ground. The index value of coral fish diversity in the coral reef ecosystem at all stations ranged from 0.58 to 3.60 where the diversity index value was in the low to medium category. The uniformity index is included in the medium category with values ​​ranging from 0.58 to 0.63 which illustrates that the difference in the number of individuals for each species is not too significant. The dominance index of reef fishes at the observation station is very small, ranging from 0.03 - 0.07 which indicates that the dominance of the species is very low, so that the condition of the reef fish community is relatively stable.